2008
DOI: 10.1016/s0140-6736(08)60954-x
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance treatment with buprenorphine and naltrexone for heroin dependence in Malaysia: a randomised, double-blind, placebo-controlled trial

Abstract: Background-Expanding access to effective treatments for heroin dependence is a global health priority that will also reduce HIV transmission. This study compares the efficacy for maintaining heroin abstinence, preventing relapse, and reducing HIV risk behaviors of three common treatments: detoxification followed by drug counseling only or drug counseling combined with opioid antagonist (naltrexone) or agonist (buprenorphine) maintenance treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
76
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(79 citation statements)
references
References 34 publications
3
76
0
Order By: Relevance
“…The expansion of services has resulted in an estimated 7,000 individuals currently receiving treatment [14]. Research studies of MAT in Malaysia have compared naltrexone treatment to buprenorphine maintenance treatment in a randomized controlled trial and found that buprenorphine was superior in treatment retention to oral naltrexone [126].…”
Section: Australiamentioning
confidence: 99%
“…The expansion of services has resulted in an estimated 7,000 individuals currently receiving treatment [14]. Research studies of MAT in Malaysia have compared naltrexone treatment to buprenorphine maintenance treatment in a randomized controlled trial and found that buprenorphine was superior in treatment retention to oral naltrexone [126].…”
Section: Australiamentioning
confidence: 99%
“…A full review of these therapies is beyond the scope of this article; however, several relevant reviews exist (Magura et al, 2007;Schottenfeld, Chawarski, & Mazlan, 2008). Agonist MAT involves pharmacological substitution of the opioid of abuse with controlled dosing of a long-acting opioid, which reduces cravings and the likelihood of relapse (Bell, Burrell, Indig, & Gilmour, 2006).…”
Section: Treatment Options For Od Patientsmentioning
confidence: 99%
“…The relationship between treatment outcomes and adherence with medication has been documented within many diseases, including addiction (Cramer et al, 2003;Schottenfeld et al, 2008). Results largely indicate that patients with chronic diseases who are adherent with their medication regimen tend to have better outcomes (Dolor et al, 2009).…”
Section: Treatment Options For Od Patientsmentioning
confidence: 99%
“…Buprenorphine is effective in treating opioid use disorder (Ling et al, 1998, Fudala et al, 2003, Fiellin et al, 2006, Schottenfeld et al, 2008) and is considered an essential medication for this indication (World Health Organization, 2013). Since receiving Food and Drug Administration approval in 2002, buprenorphine has significantly increased treatment capacity for opioid use disorder in the U.S. (Arfken et al, 2010, Greene, 2010).…”
Section: Introductionmentioning
confidence: 99%